Insider's Guide to Film Finance - Alberstat, Philip (Routledge, 2012)
Financing an independent feature film production is a highly complex process. This book demystifies the legal and commercial implications of a film from start to finish. It provides a detailed survey of each of the processes and players involved, and analyses of the legal and commercial issues faced by all of the participants in a film financing transaction. Packed with legal advice and straight forward explanations this is an essential reference for filmmakers worldwide. With contributions from leading professionals around the world, and an up-to-date international approach, this is an invaluable tool for producers, and others involved in the film industry. Includes: Case studies, Sample Recoupment Schedules, Alternative Financing Models, Glossary of Film Financing and Banking Terms Philip Alberstat is a media finance and production lawyer specialising in film, television and broadcasting. He has worked on films such as The 51st State, Goodbye Mr Steadman, Tooth and numerous television programmes and series. He is on the editorial board of Entertainment Law Review and is the author of The Independent Producers Guide to Film and TV Contracts (2000), and Law and the Media (2002). Philip is involved in raising finance for film and television productions and negotiating and structuring film and television deals. He undertakes corporate and commercial work and handles the intellectual property aspects of broadcasting and finance transactions. He has also executive produced numerous film and television productions. He won an Emmy Award in 2004 as an Executive Producer of the Film, "The Incredible Mrs. Ritchie". Philip joined Osborne Clarke as a partner in February 2002. Prior to that he was Head of Legal and Business Affairs with one of the largest independent TV production companies in the UK. He was previously Head of Media at Baker and McKenzie and began his career at Olswang. He was winner of the Lawyer/Hifal Award for Solicitor of the year in 1997 and is listed in Legal Experts in the area of Film Finance/Media.